2017
DOI: 10.1007/s11239-017-1520-2
|View full text |Cite
|
Sign up to set email alerts
|

Prothrombotic genetic risk factors in patients with very early ST-segment elevation myocardial infarction

Abstract: The contribution of prothrombotic genetic risk factors in the pathogenesis of premature acute myocardial infarction (MI) is controversial. We examined the prevalence of prothrombotic polymorphisms (G1691A of factor V gene [FV Leiden] and G20210A of prothrombin [FII] gene), deficiencies of natural anticoagulants (protein C, protein S and antithrombin III) and antiphospholipid syndrome (APS) in patients with early ST-segment elevation MI (STEMI). We recruited 255 consecutive patients who had survived a STEMI ≤ 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 33 publications
1
15
0
6
Order By: Relevance
“…A study conducted among 337 patients of heterozygous protein C deficiency showed the prevalence of arterial thrombosis in only 7.1% of subjects [9]. A recent work involving 255 consecutive patients, who had endured a STEMI in <35 years of age, revealed protein C deficiency in only one of them (0.4%) [10]. A cohort family study revealed arterial events in only 8% of the 144 subjects with protein C and protein S deficiency [11].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among 337 patients of heterozygous protein C deficiency showed the prevalence of arterial thrombosis in only 7.1% of subjects [9]. A recent work involving 255 consecutive patients, who had endured a STEMI in <35 years of age, revealed protein C deficiency in only one of them (0.4%) [10]. A cohort family study revealed arterial events in only 8% of the 144 subjects with protein C and protein S deficiency [11].…”
Section: Discussionmentioning
confidence: 99%
“…A study comprising of 337 patients with heterozygous PC deficiency showed arterial thrombosis in only 7.1% of the subjects [11]. A recent work involving 255 patients with ST-elevation MI in <35 years of age, revealed a deficiency of PC in only one of them (0.4%) [12]. A cohort study highlighted arterial thrombotic events in only 8% of the 144 patients with deficiencies of both PC and PS [13].…”
Section: Figure 5: the Homeostasis Between Procoagulants And Anticoagmentioning
confidence: 99%
“…В исследовании, включавшем 400 здоровых добровольцев и 255 больных ОИМпST моложе 35 лет, не выявлено различий по частоте носительства лейденовской мутации; определялось увеличение риска развития ОИМпST при сочетании носительства полиморфизма G20210A и курения. Вклад протромботических расстройств, таких как недостаточность протеинов С, S и антитромбина III, у исследованных больных был незначительным [40]. В проведенном ОСТРЫЙ КОРОНАРНЫЙ СИНДРОМ § нами исследовании снижение активности антитромбина III и протеина С выявлялось у 4 (13 %) больных в течение 1-х суток после индексного события и не определялось через 1 год.…”
Section: нака -невыраженный атеросклероз коронарных артерийunclassified